2020
DOI: 10.35508/mkm.v2i1.2027
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Intervensi Makanan Tambahan Padat Energi dan Protein Berbasis Pangan Lokal terhadap Perbaikan Status Gizi Balita

Abstract: Malnutrition problems that mostly occur in NTT are particularly caused by low protein intake. Therefore, this study was designed to intervene in feeding energy and protein dense snack to improve the nutritional status of children under five. This research was conducted in Tanah Putih Village, Kupang Tengah Sub-district, Kupang District. The research was an experimental method with a completely randomized design. Three types of intervention were given, namely: p1 = cassava + skipjack fish; p2 = cassava + rice b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This research is not in line with research conducted by Aspatria in Tanah Putih Village, Tanah Tengah District, Kupang Regency, which showed that after being given additional food intervention for 30 days, there was a process of changing the nutritional status of toddlers in a better direction, seen from the z-score value of toddlers with indicators. BW/TB after intervention was significantly (p<0.05) higher than before intervention (Aspatria, 2020).…”
Section: Resultsmentioning
confidence: 73%
“…This research is not in line with research conducted by Aspatria in Tanah Putih Village, Tanah Tengah District, Kupang Regency, which showed that after being given additional food intervention for 30 days, there was a process of changing the nutritional status of toddlers in a better direction, seen from the z-score value of toddlers with indicators. BW/TB after intervention was significantly (p<0.05) higher than before intervention (Aspatria, 2020).…”
Section: Resultsmentioning
confidence: 73%